Prevalence of schizophrenia and related disorders in Malaga (Spain): results using multiple clinical databases. (15th October 2014) - Moreno-Küstner, B.; Mayoral, F.; Navas-Campaña, D.; García-Herrera, J. M.; Angona, P.; Martín, C.; Rivas, F.
Abstract : Background: To calculate the 1-year prevalence of schizophrenia and related disorders in a catchment area of Malaga (Spain) and determine the prevalence by gender, dwelling (rural or urban) and socioeconomic area (deprived or non-deprived area). Method: This cross-sectional study comprised the mental health area covered by Carlos Haya Hospital. We used multiple large clinical databases and key informants to identify cases. Results: The mean 1-year prevalence of schizophrenia and related disorders was 6.27 per 1000. It was nearly double in men (8.45 per 1000) than in women (4.26 per 1000) ( p  < 0.001), with a male-to-female ratio of 1.98. The rate was higher in urban (6.64 per 1000) than rural areas (3.95 per 1000) ( p  < 0.0001) and in socioeconomic deprived areas (7.56 per 1000) than non-deprived areas (6.12 per 1000) ( p  = 0.005). For the subgroup of schizophrenia, the rates were: men, 5.88 per 1000 and women, 2.2 per 1000 ( p  < 0.0001), with a male-to-female ratio of 2.67. The rate was also higher in urban (4.2 per 1000) than rural areas (2.49 per 1000) ( p  < 0.0001) and in socioeconomic deprived areas (4.49 per 1000) than non-deprived areas (3.9 per 1000) ( p = 0.149). Conclusions: The use of multiple clinical sources of information not only from mental health services, but also from emergency departments, primary care and private settings revealed high prevalence rates of schizophrenia and related disorders. This diagnosis is more common in men and in cities. Such precise estimates of the prevalence of schizophrenia have important repercussions for resource allocation and policy planning.